BAGAIMANA BERBAGI INFORMASI MEMEDIASI PENGARUH KUALITAS INFORMASI TERHADAP KINERJA MANAJEMEN RANTAI PASOKAN : HOW INFORMATION SHARING MEDIATES THE INFLUENCE OF INFORMATION QUALITY ON SUPPLY CHAIN MANAGEMENT PERFORMANCE - Aji, Ridho Pramana; Silfi, Alfiati; Hilmi, Hilmi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This study aims to examine the factors that influence supply chain management performance, focusing on information sharing as a mediating factor. The population of this study was 13,540 MSMEs in Pekanbaru City, with sample selection using convenience sampling. A 5-point scale was used, and considering the social scale of this study, 36 statements were multiplied by 5, resulting in a sample size of 180 respondents. The statistical method used was Partial Least Square (PLS) implemented through SmartPLS. Data analysis revealed that information quality has a significant impact on supply chain management performance, information quality affects information sharing. In addition, information quality affects supply chain management performance through information exchange. This study highlights the importance for MSMEs to understand the role of information quality in improving supply chain performance and the role of information sharing in improving supply chain efficiency.